Effect of different methods of defoliation on growth, flowering and yield in lasora (Cordia myxa L.) (Indian Journal of Arid Horticulture, 2018)
Lasura (Cordia myxa L.) popularly known as Gonda of number of flower emerged. Number of days taken to  or Lehsua is an underutilized fruit crop grown in arid and semi maturity stage of fruit from date of defoliation was counted as  arid region of India and worldwide. In Rajasthan, flowering maturity of fruits days after defoliation. The yield/plant was  occurs in 10th March to 23rd April under Jodhpur condition calculated by sum of weight obtained from all the pickings and  with new leaves (Vashishtha et al., 1985). In Rajasthan yield/ha. was calculated by multiplying the yield per plant  especially in western Rajasthan demand of lasura fruit is with number of plants (278) per ha. Fruit weight was  increases near the festival of 'Holi' or in month of March. But, calculated by average of five fruits from each treatment.  the availability of fruit in market is in month of May. Statistical analysis was carried out as per methods prescribed  Defoliation of leaves in lasura in the month of December- by Panse and Sukhatme (1985).
Keywords: western Rajasthan; leaves in lasura; December